Blind trust in unblinded observation in Ecology, Evolution, and Behavior - Kardish, Melissa R.; Mueller, Ulrich G.; Amador-Vargas, Sabrina; Dietrich, Emma I.; Ma, Rong; Barrett, Brian; Fang, Chi-Chun (Frontiers in Ecology and Evolution, 2015)
We survey 492 recent studies in the fields of ecology, evolution and behavior (EEB) to evaluate potential for observer bias and the need for blind experimentation in each study. While 248 articles included experiments that could have been influenced by observer bias, only 13.3% of these articles indicated that experiments were blinded. The use of blind observation therefore was either grossly underreported in the surveyed articles, or many EEB studies were not blinded. We hope that a concerted effort of the field of EEB – including researchers, peer-reviewers, and journal editors – will help promote and institute routine, blind observation as an essential standard that should be practiced by all sciences.